Stability of cylindrical panel with variable thickness - Luong, Nguyen Thi Hien; Hoach, Thach Som So (Vietnam Journal of Mechanics, 2006)
A linear buckling analysis based on the small deflection theory is presented for the cylindrical panel with sinusoidal changes in the shell thickness. The buckling load for simply supported cylindrical panel around the periphery is defined by using the hybrid perturbation - Galerkin method. The influence of the thickness variation parameter on the critical loads is investigated.